2005
DOI: 10.1111/j.1365-2958.2005.04571.x
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli EspG disrupts microtubules and in conjunction with Orf3 enhances perturbation of the tight junction barrier

Abstract: EspG, a secreted effector of enteropathogenic Escherichia coli (EPEC), as well as its homologue Orf3, has been shown to disrupt microtubules (MTs) in fibroblasts and non-polarized epithelial cells. The roles of MTs and the effects of MT disruption in these cell types differ significantly. The aim of this study was to investigate the effects of EspG on polarized, host target intestinal epithelial cells. Immunofluorescent labelling of tubulin showed that EPEC caused progressive fragmentation and loss of the MT n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(128 citation statements)
references
References 67 publications
4
118
2
4
Order By: Relevance
“…36 Other molecules that perturb barrier function independent of espF include mitochondria-associated protein 37 and espG in conjunction with orf3. 38 Our findings demonstrate that infection of human intestinal epithelial cells with C. rodentium results in disruption of AJC structure and barrier function. These findings are consistent with a recently published report demonstrating that infection of murine intestinal epithelial cells with C. rodentium resulted in diminished barrier function associated with disruption of TJ expression of claudins-4 and -5.…”
Section: Discussionmentioning
confidence: 83%
“…36 Other molecules that perturb barrier function independent of espF include mitochondria-associated protein 37 and espG in conjunction with orf3. 38 Our findings demonstrate that infection of human intestinal epithelial cells with C. rodentium results in disruption of AJC structure and barrier function. These findings are consistent with a recently published report demonstrating that infection of murine intestinal epithelial cells with C. rodentium resulted in diminished barrier function associated with disruption of TJ expression of claudins-4 and -5.…”
Section: Discussionmentioning
confidence: 83%
“…Amieva and colleagues have reported that Helicobacter pylori causes a similar recruitment of ZO-1 to the bacterial attachment sites in Madin-Darby canine kidney (MDCK) cell monolayers and proposed that the recruitment is linked to a dysfunctional paracellular seal (1). Because EPEC has been reported to affect the integrity of the epithelial barrier (11,32,34,36,37,43,54), we examined if the EPEC-induced recruitment of ZO-1 is also linked with the disruption of the barrier. A polarized Caco/B7 monolayer was infected with wild-type EPEC and the mutants, and the TER across the monolayer, which is a hallmark of the integrity of the epithelial barrier, was measured.…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that all members of the EspG family exhibit cysteine protease-like activity (Tomson et al 2005;Smollett et al 2006;Yoshida et al 2006). In a similar assay, we investigated the ability of VirA to degrade a/b-tubulin.…”
Section: Resultsmentioning
confidence: 99%